El aumento en el reconocimiento local a la protección de la biodiversidad a través de otras medidas de conservación eficaces basadas en áreas. Especial énfasis en el Ártico: A Special Emphasis on the Arctic - Sellheim, Nikolas (Revista Tribuna Internacional, 2019)
At the 10th Conference of the Parties (CoP) of the Convention on Biological Diversity (CBD) in 2010. the so-called Aichi Biodiversity Targets were adopted. In Target 11, states are to use protected areas and ‘other effective area-based conservation measures’ (OECMs) to achieve quantitative goals of biodiversity protection. However, only at CoP14 in 2018 a definition of OECMs was put in place. This paper presents how despite the absence of a definition countries and organisations have made use of OECMs in their endeavours to protect biodiversity. Focusing particularly on Arctic countries, it is shown that OECMs constitute an important tool for indigenous and local recognition and how the discourse within the CBD has made increasing reference to indigenous and local communities. It is furthermore discussed how OECMs, despite challenges of application, can contribute to a redefinition of ‘conservation’ and to the reaching of biodiversity targets 2020 and beyond.